The influence of financial distress, family influence, peer influence, life satisfaction on saving money among malay in Malaysian Public Sector - Mohamed, Ahmad Martadha (exeliq publishing, 2018)
Savings has been found to be low among Malaysians, especially among the working households. Previous research has revealed that there is a change in the pattern of savings and investment of the people due to the rapid economic transformation from resource-based to market-based economy. This study aims to examine the influence of financial distress, family influence, peer influence and life satisfaction on the attitude towards savings among Malay employees in Malaysian public sector. For the sampling technique, a random selection of employees in Malaysian government sector will be applied in this study. Overall, this study aims to obtain total of 860 respondents to be participated in this study. Hence, this study provides knowledge about the pattern of savings among the public sector employees and enables individuals to make savings that can secure their future life.